Proposta de um sistema hipermídia adaptativo educacional para a personalização do processo de ensino atraves da web - Bueno, Alexandre Martins Ferreira (2011)
Nowadays, e-learning has become an important source of knowledge, providing content without the limitation of time or space. In this context, Web-based education became an important sector. A large number of e-learning applications have utilized the Web to teach, mainly to provide distance learning. As a result of the substantial growth in elearning there has been an increase in the diversity of students that uses this environment to achieve their academic or professional backgrounds. In general, these students have di erent personal, social-cultural and cognitive characteristics. Adaptive Hypermedia Systems provide resources to assist this diverse public, they are able to consider the individual characteristics of students during the learning process. It is known that the representation of these features are often associated with uncertain and imprecise information. Given this context, this work proposes a Web-based Adaptive Educational Hypermedia System (with instructional content) that aims to personalize the process of distance learning. It has a student model that is able to represent the uncertainties related to the student's knowledge (characteristic of the students considered by the system) through the use of a Bayesian Network. This model is adjusted according to the answers provided by students in ability tests, which in turn are evaluated by a mathematical model of Item Response Theory. The experiment realized compared the results obtained by the proposed system, that is provided with adaptation (personalization) mechanisms, and other system that has no such mechanisms, in which the same content was presented to all the students. Statistical analysis of the collected data has shown a signi cant improvement in knowledge retention by the students who used the system provided with adaptation. However, it was expected, as a result of this improvement, that the levels of satisfaction reported by the students who used the proposed system were better than the levels reported by the students who used the system without adaptation, which was not evidenced by the gathered data.